Efficiency Of Developing Communicative Competence In Teaching Foreign Languages Through Innovative Approaches (Texas Journal of Philology, Culture and History, 2024)
This article is devoted to develop foreign language communicative competence and reaching shared goals or stumbling over small misunderstandings can be determined by effective communication, creative approaches enhance both English and oral communication competences. A part from it, the article highlights the ability to communicate effectively and responsibly in a real-world context in order to impart knowledge, opinions, attitudes, or ideas to others is known as speaking ability of young learners